Diagnostic Utility of Brain MRI Volumetry in Comparing Traumatic Brain Injury, Alzheimer Disease and Behavioral Variant Frontotemporal Dementia. (20th December 2022) - Raji, Cyrus A.; Meysami, Somayeh; Porter, Verna R.; Merrill, David A.; Mendez, Mario F.
Abstract: Background: Application of brain MRI with volumetric quantification can improve delineation of various neurocognitive disorders. Method: We utilized 136 participants from previously defined cohorts of traumatic brain injury (TBI; n=40) [1], early (EOAD; n=45) and late onset Alzheimer disease (LOAD; n=31) [2] as well as of behavioral variant frontotemporal dementia (bvFTD; n=20). Participants had brain MRI including 3D T1 sequences amendable to volumetric quantification. Scans were analyzed with an FDA cleared software program, Neuroreader[3] to measure regional brain volumes. At the time of analysis, Mini‐Mental State Exam (MMSE) scores were available on majority of participants (n=125). One‐way ANOVA compared mean age, MMSE, and brain volumes across all four groups with Bonferroni correction for multiple comparisons. All brain volumes were corrected for total intracranial volume (TIV). Discriminant analysis was done with leave‐one‐out cross validation on measured brain volumes to determine diagnostic delineation across groups. Automated linear regression identified predictive features from these quantified structures. Result: Participant demographics and MMSE scores are shown in Table 1. With respect to age, LOAD was the oldest compared to other groups (p<.001). There were no statistically significant differences in sex (p=.58) with women comprising 54.4% of the entire sample. EOAD and LOAD had the lowest MMSE scores compared to TBI (p=.04 for EOAD and p=.01 for LOAD). Regional volume difference across groups showed lowest hippocampal volumes in LOAD (p=.005), low white matter volume in TBI (p=.007), lower parietal lobe volumes in EOAD (p<.01), and lower frontal lobe volumes in bvFTD (p<.001). Regional volume differences resulted in a correct classification of 89%, 79.4% after cross validation. Predictive features included caudate, amygdala, frontal, parietal, temporal lobar and total white matter volumes. Conclusion: We identified the diagnostic utility of regional volumetric differences across multiple neurodegenerative and non‐neurodegenerative disorders. The lower parietal lobe volumes in EOAD and lower hippocampal volumes in LOAD and well as frontal atrophy of bvFTD reflect the known anatomical distribution of pathology in those conditions[4]. The white matter volume loss in TBI is a previously demonstrated feature of that condition[5]. Brain MRI volumetry may therefore be beneficial in clinical practice.